Dualism between body and soul in the pentecostal theology - Albano, Fernando (2011)
The object of this research is the dualism between body and soul in the Brazilian Pentecostal theology, represented by its major expression: the Assembly of God Church. Thus, from the appreciation of the whole human being, it seeks to investigate the Pentecostal theological anthropology, its tensions and convergences with the biblical perspective. The theological emphasis on the unity of the human constitution, which the biblical testimony indicates, contrasts with the historical experience of Christianity, in which the body always played a secondary status, which remains in Pentecostalism today. Finally, it indicates a Pentecostal theology the adoption of the anthropological unity perspective.